1980
DOI: 10.1016/0020-1790(80)90057-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glycogenolysis in the locust fat body during flight

Abstract: Abstract~Glycogen reserves in the fat body of Locusta migratoria decrease dramatically during the first two hours of flight. In fat body of rested locusts only 10~o of glycogen phosphorylase occurs in the active form. The enzyme is activated significantly during flight, when up to one-third of the total phosphorylase becomes active. Plaosphorylase activation can also be accomplished by injection of corpus cardiacum extracts, to give a maximum of circa 75~o active enzyme. Locust fat body is shown to contain pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In Locusta, flight activity as well as corpora cardiaca extracts elevate the level of cAMP in fat body (G/ide and Holwerda, 1976), which also contains cyclic nucleotide-dependent protein kinase (Pines and Applebaum, 1978;Van Marrewijk et al, 1980). However, the actual mechanism of phosphorylase activation by adipokinetic hormone still remains to be elucidated.…”
Section: Hormonal Control Of Trehalose Mobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Locusta, flight activity as well as corpora cardiaca extracts elevate the level of cAMP in fat body (G/ide and Holwerda, 1976), which also contains cyclic nucleotide-dependent protein kinase (Pines and Applebaum, 1978;Van Marrewijk et al, 1980). However, the actual mechanism of phosphorylase activation by adipokinetic hormone still remains to be elucidated.…”
Section: Hormonal Control Of Trehalose Mobilizationmentioning
confidence: 99%
“…The steady state of haemolymph trehalose is sustained by the mobilization of other carbohydrate stores. Fat body glycogen is the main source, its concentration decreasing at a rate sufficient to account for almost two-thirds of the total trehalose utilized between 30 and 120min of flight (Van Marrewijk et al, 1980). Thus one-third must be derived from other sources, part of which will be provided by the glycerol that is liberated by hydrolysis of diacylglycerol, as will be discussed in section 5.2.…”
Section: Mobilization Of Carbohydrate Storesmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycogen phosphorylase activity was measured spectrophotometrically in the direction of glycogen degradation as described previously (Van Marrewijk et al, 1980a). Active phosphorylase was assayed in the absence of Y-AMP, whereas total phosphorylase was measured in the presence of 2 mM Y-AMP.…”
Section: Determination Of Phosphorylase Activitymentioning
confidence: 99%
“…Extracts from corpora cardiaca (CC), and synthetic adipokinetic hormone (AKH) evoke hyperlipaemia in locusts also, but they have no influence on haemolymph carbohydrate levels (for reviews, see Beenakkers et al, 1981aBeenakkers et al, , b, 1983. However, in the locust fat body flight activity results in the activation of glycogen phosphorylase, the enzyme determining the rate of glycogenolysis (Van Marrewijk et al, 1980a), This phosphorylase activation is needed to meet the enhanced turnover rate of haemolymph trehalose during sustained flight . Fat body phosphorylase is also activated upon injection of CC-extracts (Bcenakkers et al, 1978), and recently this effect of the CC on phosphorylase was shown to be due virtually entirely to AKH (Van Marrewijk and Beenakkers, 1982;.…”
Section: Introductionmentioning
confidence: 99%